A Mixed Firm Objective Function: Some Instances of Bizarre Behaviour - Flavio Delbono; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
We analyse the objective function of a mixed firm, i.e. a firm whose controllers have different objectives (profit and value added per worker). It seems that the optimal output behaves in a bizzarre manner near critical values of a weight parameter. Output jumps up or down whenever we approach the critical value respectively from above or from below.
Keywords: 330